2011
DOI: 10.1007/s11434-011-4498-8
|View full text |Cite
|
Sign up to set email alerts
|

High lake levels on Alxa Plateau during the Late Quaternary

Abstract: Field investigations including lake shoreline measurement and 14 C chronology have been carried out on the Alxa Plateau to better understand the formation and evolution of the high lake levels in northwest China during the late Pleistocene. Comprehensive field investigations show that there are at least ten shorelines at different elevations at Juyan Lake, at least four on the northwest side of the Jilantai Salt Lake, and nine shorelines and one terrace on the northeast margin of Zhuye Lake. Stratigraphic corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…1). Research by Zhang et al (2002) and Wang et al (2011) on the Tengger Desert (adjacent to the study region) indicated that, because of climate change, the water levels in the palaeolake present in the area Fig. 1. (a) Study region location (b) potential sand transport, and sand transport direction in the study region.…”
Section: Study Regionmentioning
confidence: 99%
“…1). Research by Zhang et al (2002) and Wang et al (2011) on the Tengger Desert (adjacent to the study region) indicated that, because of climate change, the water levels in the palaeolake present in the area Fig. 1. (a) Study region location (b) potential sand transport, and sand transport direction in the study region.…”
Section: Study Regionmentioning
confidence: 99%
“…Furthermore, he deduced lake expansion during the late and middle Holocene (Yang et al, 2011;Yang and Scuderi, 2010). Recently, we have demonstrated the late Quaternary high lake-level and large lake stage in Alxa Plateau (Wang et al, 2011). Nevertheless, the lack of field studies and scientific profile samples, and especially the inexistent research on hydrologic budget, lead to a void in exploring the changes in spatial patterns regarding paleo-hydrological or paleo-climatic features.…”
Section: Introductionmentioning
confidence: 99%
“…The deserts and sand fields have changed greatly in time and space during late Quaternary, and to reconstruct spatial changes in extent of active dunes is particular important [2][3][4][5][6]. There were a few reconstructions of desert changes during the Last Glacial Maximum (LGM) and Holocene Optimum (HO) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], however, because of limited dating work and field investigation, the results need tested. Moreover, some previous reconstructions were speculation based on comparison with paleoclimatic records, without direct and specific stratigraphic evidence; therefore, the conclusions [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] should be clarified.…”
mentioning
confidence: 99%
“…There were a few reconstructions of desert changes during the Last Glacial Maximum (LGM) and Holocene Optimum (HO) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], however, because of limited dating work and field investigation, the results need tested. Moreover, some previous reconstructions were speculation based on comparison with paleoclimatic records, without direct and specific stratigraphic evidence; therefore, the conclusions [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] should be clarified. In China, some early investigations have advanced our knowledge of environment changes in the desert and sand fields, but there were quite a few issues that were not well resolved in this previous research, including: (1) Because of the limitation of dating techniques, accurate, independent high-quality ages for the deserts and sand fields were limited in number; previous research always compared the sand deposition with established time series such as that of Chinese loesspaleosol sequence and marine oxygen isotope stages to obtain age control [9,…”
mentioning
confidence: 99%
See 1 more Smart Citation